SUPERVISION OF PREDATORY PRICING ON E-COMMERCE TRANSACTIONS IN INDONESIA - Made Lia Indah Sari; Dewa Gede Rudy (Transpublika Publisher, 2022)
This study aims to determine the legal arrangements for predatory pricing in e-commerce transactions in Indonesia, as well as to determine the supervision of predatory pricing in e-commerce transactions in Indonesia. The method used in this research is to use a review of the literature study known as the normative legal research method. The approach used is the case approach, the statutory approach and the legal concept approach which aims to provide a legal view of the vacuum of norm issue due to the lack of affordability of regulations that strictly regulate the eradication of predatory pricing in e-commerce transactions. The analysis technique used is descriptive technique. The predatory pricing method is getting more complex with the presence of e-commerce which is classified as part of business actors who run their business subject to the Anti-Monopoly Law. Predatory pricing in Article 20 of the Anti-Monopoly Law focuses on the intention of eliminating competition which should support the nation's economic development, so that it is contrary to the objective of protecting business competition activities. Supervision of predatory pricing action refers to the basis of the regulation contained in the Anti-Monopoly Law, so based on Article 30 and Article 31 of the law, it shows that there is attributive authority to KPPU as an independent institution to supervise and maintain the business competition climate in Indonesia. The KPPU's efforts to supervise predatory pricing in e-commerce transactions can only be carried out when it is clear that the e-commerce with the benefits is carried out in the jurisdiction of the Republic of Indonesia. If predatory pricing occurs, KPPU has the authority to take actions as outlined in Article 36 of the Anti-Monopoly Law.